Historical Aspects and Current Reflections of Global Economic Crisis - Hitov, Mitko (Research Papers, 2014)
This study analyzed the causes and mechanisms of functioning of the global economic crisis of the system that existed in the past centuries and was based on the financing of scientific and technical progress through lending at interest and to the constant expansion of capital. In the study applies fundamentally different approach that relations between developed and developing countries should be seen as an interaction between economic systems with varying degrees of technological division of labor. Is analyzed the role of the monetary system as an exogenous factor with regard to the real economy, who ensuring the normally flowing of the interaction between systems with different levels of technological division of labor. Are examined the historical aspects of the development of the global economic system that underlie the global economic crisis. It made fundamental conclusion that the limiting factor, who has reached his end, is the inability to further increase the productivity of labor, which until now was growing due to the increasing levels of technological division of labor. The last has reached such limiting levels, relating to an uncontrollable increased ambiguity, in the temporal and spatial aspects, after which follows technological regress. Are offered, for an initial discussion, potential methods for managing the national economy that would mitigate the impact of the crisis and would ensure more stable flowing of the social and political processes.